Sisi Gelap Investasi: Menghindari Kebangkutan Pada Investasi dan Pembayaran Kekinian - Yuliana Friska; Ani Kusumaningsih; Moh. Thoyib Safi’i; Angga Hidayat (LPPM Universitas Dharma Andalas, 2022)
The rise of various investment and payment offers loaded with the lure of high returns is undoubtedly very attractive to investors. However, recently there have been many incidents related to investment and payment. Due to the risk of investment and payments that cause investors to be deceived or bankrupt (due to a lack of understanding about suitable investments), it is necessary to socialize and enlighten investors, especially those new to the investment world. With this background, a webinar, “The Dark Shadows of Investment and Payments,” was organized to socialize and provide potential investors with knowledge. This activity is also accompanied by fundraising through continuous community service to help students in need to achieve the high quality of education. The donations collected through this webinar were then distributed as scholarships to students who need tuition assistance. This scholarship is prioritized for an underprivileged student.